Security and trends in wireless identification and sensing platform tags : advancements in RFID - Peris Lopez, Pedro, 1978-; Hernandez-Castro, Julio C., 1972-; Li, Tieyan (Information Science Reference, 2013)
"This book highlights new research regarding wireless identification and sensing platform (WISP) tags, security, and applications, serving as a reference on WISP technology and presenting recent advances in this field"--Provided by publisher
"Premier reference source"--Cover
Keywords: Wireless sensor networks.; Radio frequency identification systems.; Wireless sensor networks -- Security measures.; Radio frequency identification systems -- Security measures.; elektronické knihy; electronic books